Interaction between icts and bilingual teaching - Amaya Ardila, Jasmid; Carvajal, Ángela Patricia; Silva Bothia, Carolina (Rastros Rostros, 2012)
This project is based on the use of icts in education, in the development of the “primaria bilingüe” (bilingual primary education) project, currently under course in 5th and 6th grade of the Escuela Normal Superior de Bucaramanga. This is a research paper resulting from the macro-research “Interaction between icts and bilingual teaching as a functional learning alternative”, developed from the second half of 2010 to thefirst half of 2012. In this project, we intend for students to learn and acquire a second language in a comprehensive and continuous context, as a result of all their curricular subjects being taught in English, all this with constant support from a teacher. Through the use of a wiki, students can give feedback on topics covered in class, they are also involved so they can share and interact. In this process we can see the progress in the students’ English level based on the parameters of the Common European Framework
Keywords: clil; bilingualism; icts; wiki